2020
DOI: 10.1002/htj.21883
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional turbulent forced convection around a hot cubic block exposed to a cross‐flow and an impinging jet

Abstract: A numerical study of a three-dimensional, turbulent, forced convection flow around a hot cubic block exposed to cross-flow and an impinging jet is carried out. The standard k-ε turbulence model is used to study the effects of Reynolds number ratio on the flow and heat transfer. For each value of the Reynolds number of the jet, the Reynolds number ratio is equal to 1, 1.5, and 2. The influence of the channel height and the jet axis location are also examined. The governing equations are solved by using Ansys Fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Research on the impinging of slot jets in a confined channel loaded with metal foam using Al 2 O 3 -water nanofluids was performed by Bianco et al Findings showed that the presence of nanofluids helps to increase the heat transfer coefficient. Through the discussion of the previous literature review described above, we discovered that air was used as a working fluid in all previous studies, 14,17,29,30,[46][47][48] that were conducted on the configuration of a hot cube situated in the center of the lower surface of a horizontal channel, where this cube is subjected to a horizontal liquid and an impinging jet affecting its upper face.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research on the impinging of slot jets in a confined channel loaded with metal foam using Al 2 O 3 -water nanofluids was performed by Bianco et al Findings showed that the presence of nanofluids helps to increase the heat transfer coefficient. Through the discussion of the previous literature review described above, we discovered that air was used as a working fluid in all previous studies, 14,17,29,30,[46][47][48] that were conducted on the configuration of a hot cube situated in the center of the lower surface of a horizontal channel, where this cube is subjected to a horizontal liquid and an impinging jet affecting its upper face.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers discovered that the horizontal flow with an impinging jet structure could enhance heat transfer better than a non-impingement jet. Boudraa and Bessaïh 30 analyzed the flow behavior and heat transfer over a hot block. It was discovered that a change in the position of the jet to the channel inlet could boost the heat transfer rate.…”
Section: Introductionmentioning
confidence: 99%